The Relationship Between Islamic Social Finance and Green Economy Development in Muslim-Majority Countries - Naz'aina Naz'aina; Muhamad Nasrip; Nosirjanov Shokhrukh Tokhir Ugli (International Forum of Researchers and Lecturers, 2024)
This study investigates the role of Islamic social finance in supporting green economy development across Muslim-majority countries. Islamic social finance instruments, including zakat, waqf, and sadaqah, are designed to redistribute wealth ethically and address social inequalities, while also offering potential for financing environmentally sustainable projects. Using a quantitative research design and econometric modeling with panel data, the study analyzes the impact of these instruments on environmental performance indicators such as the Green Economy Index (GEI) and Environmental Performance Index (EPI). Secondary data are collected from international sources including the OIC Statistical Database, the World Bank, and the Islamic Development Bank, covering selected countries such as Indonesia, Malaysia, Saudi Arabia, Turkey, Pakistan, and Egypt. The analysis includes independent variables representing zakat distribution, waqf assets, and sadaqah volume, with control variables including GDP per capita, governance indicators, and population growth. Descriptive statistics reveal substantial variation in Islamic social finance and environmental performance across countries, indicating the importance of institutional governance and policy integration. Econometric results demonstrate a positive correlation between zakat and waqf development and environmental performance, while sadaqah contributes positively but to a lesser extent. These findings suggest that Islamic social finance can directly support environmental projects, including renewable energy initiatives, sustainable agriculture, and green infrastructure, complementing conventional fiscal tools. The study highlights the advantages of Islamic social finance in promoting justice, sustainability, and ethical allocation of resources, and it emphasizes the need to integrate green objectives into zakat and waqf operational frameworks. Policy recommendations include mainstreaming Islamic social finance into national green policies, enhancing governance and transparency, and encouraging cross-sector collaboration between financial institutions and environmental agencies. Future research is suggested to explore micro-level impacts on household and community environmental behaviors and to conduct comparative studies across regions. Overall, the study underscores the potential of Islamic social finance as a faith-driven, socially inclusive, and environmentally sustainable mechanism for supporting long-term green economic development.